Spatial Coordination Incentives for landscape-scale environmental management: A systematic review. (March 2022) - Nguyen, Chi; Latacz-Lohmann, Uwe; Hanley, Nick; Schilizzi, Steven; Iftekhar, Sayed
Abstract: Conventional agri-environmental schemes (AES) have been criticized for failing to exploit conservation synergies that could be obtained from spatial coordination of conservation efforts. Understanding the design and implementation of novel incentive mechanisms explicitly designed to boost spatial coordination of conservation efforts is, therefore, of critical importance. We conducted the first systematic review of such incentives ('Spatial Coordination Incentives'), including Agglomeration Bonus, Threshold Bonus, and Threshold Payments. The review aims to investigate these incentives' performance and identify the underlying factors affecting their performance. An extensive bibliographic search was carried out and 55 papers were included in the final analysis. Most papers (89%) are theoretical and experimental studies. Real-world applications of these incentives are rare. The theoretical and empirical evidence suggests that these incentives could potentially promote participation, spatial coordination, and environmental effectiveness. However, the results remain a subject of debate in experimental studies. Performance variation is attributed to scheme design features and contextual factors. We highlight the areas where future work would be most warranted to further validate the performance of these incentives. Insights gained from the review provide important implications for the emerging field of conservation science and ongoing efforts to improve the design of AES for better landscape-scale management. Highlights: Systematic review of incentives mechanisms for spatial coordination in conservation. A moderate number of analytical and experimental studies. Real-world applications are rare. Both design features and contextual factors influence their performance. Key knowledge gaps and priority areas for future work are identified.